BUDIDAYA JAMUR PERUSAK KAYU VI. BUDIDAYA PLEUROTUS OSTREATUS PADA DOLOK LIMA JENIS KAYU - Sihati Suprapti; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1988)
Oyster  mushroom   (Pleurotus  ostreatus)  was cultivated   on  logs of  five  wood  species,  i.e.  hamerang  (Ficus  grossularoides  Burn.f.),   jeungjing  (Albizia  falcataria (L.)  Eosb.),   jirak  (Symplocos  fasciculata  Zoll.),  kihuut   (Vernonia arborea Ham.)   and  manii (Maesopsis eminii  Engl.).The logs were kept  in a house, at Gunung Bunder Forest  Complex, Bogor (first experiment)    and  under  soka  trees  in Bogor (second  experiment).The  logs start producing   fungus  two  months  after  inoculation. After  eight month  observation, the highest yield per log was obtained  from  manii 1139.90   g (in a house) and  1171.62 g (under soka trees; and the lowest yield was on jirak (0.99 g).                                                                               Total  yield  during  the experiment   per  m  of  log,  under  soka  trees was higher than that  cultivated  in a house Manii and  hamerang  logs probably belong  to  media  for  oyster   mushroom   than  other  species